Heat transfer efficiency analysis of infant radiant warmer by 3D finite element method - Roongprasert, K.; Phasukkit, P.; Airphaiboon, S.; Pintavirooj, C.; Thongpance, N.; Sanpanich, A. (My University, 2012)
This paper presents heat transfer from infrared element source from infant radiant warmer. The principles of thermal radiate using three-dimensional finite element methods is show the efficiency and effect of Infant radiant warmer. In the design of the system has to model the underlying reality of the infant radiant warmer are used for Simulation results were similar to reality as possible. The simulation results of thermal radiation from the infrared lamp to mattress by using the three-dimensional finite element methods simulation as close to the true result. The results come in the form of temperature, temperature gradient and the direction of heat radiation into the mattress. The result can be that the effects of radiation on the skin of newborns using infant radiant warmer treatment. The results of the analysis of the principle of three-dimensional finite element methods then try to make it easy to design infant radiant warmer effective for use with newborns up. ©2012 IEEE.
Keywords: Finite element method (FEM); Heat transfer; Infant radiant warmer; Neonatology